Capsaicin-induced membrane currents in cultured sensory neurons of the rat - Vlachová, V; Vyklický, L (Physiological research, 1993)
Membrane currents induced by capsaicin (CAPS) in cultured sensory neurons from 1- to 2-day-old rats were studied. Responses to CAPS (10 microM) exceeding 1 nA at -50 mV were found in smaller, usually bipolar or tripolar neurons in which GABA (30 microM) induced small or no response. Large, unipolar neurons, which exhibited large responses to GABA, were completely insensitive to CAPS (10 microM). In contrast to GABA, responses to CAPS exhibited a slow rise and slow decay and a marked tachyphylaxis after repeated CAPS applications at high concentrations which made it difficult to study the concentration-response relationship. In partially run-down neurons, which exhibited quasi stable responses, the slope of the ascending phase was concentration-dependent with an apparent association rate constant K1 9 x 10(4) [M-1s-1]. The time constant of the decay was 3.5 s, and was concentration-independent. However, in 5 neurones the EC50 measured from the first series of CAPS applications at increasing concentrations was 0.31 +/- 0.5 microM with a Hill coefficient 1.66 +/- 0.35. The responses to CAPS reversed at +10.4 +/- 2.5 mV suggesting that the current is carried nonselectively by monovalent cations and Ca2+. The channel conductance of CAPS-gated channels at -50 mV calculated from the mean membrane current and variance of the current noise in outside-out patches or measured directly was 28 pS (n = 5). It is suggested that the CAPS-gated channels are either controlled by receptors with a very high affinity or that the channels are controlled by membrane-bound protein(s) which do not depend in their function on the supply of GTP or other intracellular metabolites.
Keywords: osmolární koncentrace; kultivované buňky; myši; potkani Sprague-Dawley; časové faktory; Cells, Cultured; myši inbrední BALB C; Rats; Cell Membrane; tachyfylaxe; Osmolar Concentration; Mice, Inbred BALB C; Ion Channels; Mice; Animals; Dose-Response Relationship, Drug; Capsaicin; GABA; zvířata; elektrická vodivost; Time Factors; Tachyphylaxis; gamma-Aminobutyric Acid; kapsaicin; krysa rodu Rattus; neurony aferentní; vztah mezi dávkou a účinkem léčiva; buněčná membrána; Neurons, Afferent; Rats, Sprague-Dawley; Electric Conductivity; iontové kanály